Creative thinking enhancement through project-based learning in science: a meta-analytic review - Hasibuan, Molani Paulina; Sunarno, Widha; Susanti VH, Elfi (International Journal of Evaluation and Research in Education (IJERE), 2025)
This research investigates the impact of project-based learning (PjBL) on enhancing students’ creative thinking abilities through a comprehensive meta-analytic study. Creative thinking is recognized as an integral part of higher-order thinking skills (HOTS) required for success. Employing the preferred reporting items for systematic reviews and meta-analyses (PRISMA), studies published between 2014 and 2024 were identified and synthesized from the Scopus database. Data analysis, conducted with R, assessed the impact of PjBL using effect size (ES) measurements. The findings demonstrate that PjBL significantly improves creative thinking skills compared to traditional teaching methods. Moderator analysis revealed that variables such as educational level, subject area, and learning model influence the outcomes, with the highest impact observed in high school and inquiry-driven subjects like physics. Variations of PjBL, including technology-enhanced models, such as Google Classroom-based approaches, further amplified its effectiveness, particularly in virtual learning environments. This study highlights PjBL’s adaptability and robust potential in fostering creativity and innovation across diverse educational contexts. The results provide practical implications for educators in designing tailored PjBL strategies to cultivate students’ creative thinking, emphasizing the importance of interdisciplinary approaches and technological integration in modern education.